2021
DOI: 10.1016/j.socscimed.2021.113982
|View full text |Cite
|
Sign up to set email alerts
|

Male out-migration and the health of left-behind wives in India: The roles of remittances, household responsibilities, and autonomy

Abstract: In developing countries, labor out-migration has led to millions of married couples living apart from each other. Male out-migration brings economic benefits to the families in places of origin, but also leads to profound changes in the lives of the left-behind wives. It is unclear how the husband's out-migration influences the health of wives, let alone the mechanisms through which any effects are transmitted. Using data from the Indian Human Development Survey (2004–2005 and 2011–2012), we estimated lagged d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…Conversely, the remittance recipients in our study have significantly lower PF probabilities than non-recipients. Though this result is counterintuitive since we expect additional resources to afford better health outcomes, a recent study found remittance recipients with poorer PF odds than non-recipients [ 18 ]. There are plausible explanations for this.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Conversely, the remittance recipients in our study have significantly lower PF probabilities than non-recipients. Though this result is counterintuitive since we expect additional resources to afford better health outcomes, a recent study found remittance recipients with poorer PF odds than non-recipients [ 18 ]. There are plausible explanations for this.…”
Section: Discussionmentioning
confidence: 99%
“…Though 60–80% of the Nigeria’s population of elderly adults require regular medical attention [ 16 ], it is surprising that only 4.7% of the received remittances go to medical expenses. There are several possible reasons for this: firstly, remittances may not be large enough to sustain a living; hence, they do not provide much to spare in terms of medical expenses [ 18 ]. Next, elderly adults might deliberately spend less on medical expenses because they prefer the cheaper and widespread traditional treatments that are available in Nigeria [ 68 , 69 ] or downplay their health challenges because of their “unrealistic optimism” in life [ 70 , 71 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations